2017
DOI: 10.17159/2310-3833/2017/v47n1a4
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in splinting the hand in children with neurological impairments

Abstract: AIM: The study aimed to explore Occupational therapy clinicians' current splinting practises in hand function intervention for children with neurological impairments within the South African context. METHODOLOGY: A quantitative cross-sectional design with use of an electronic questionnaire served to address the objectives of this study. The sample included occupational therapists working within the paediatric neurology field in South Africa. The study sample was accessed via convenience and snowball sampling i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Occupational therapists’ preferred splinting in hand function for children with neurological impairment. This finding agrees with those reported by Hepworth et al [ 30 ], who found that functional resting and neoprene thumb abduction splints are recommended in 80% of cases, anti-spasticity splints in 60% of cases, and both serpentine and supination splints in 32.5% of cases.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Occupational therapists’ preferred splinting in hand function for children with neurological impairment. This finding agrees with those reported by Hepworth et al [ 30 ], who found that functional resting and neoprene thumb abduction splints are recommended in 80% of cases, anti-spasticity splints in 60% of cases, and both serpentine and supination splints in 32.5% of cases.…”
Section: Discussionsupporting
confidence: 93%
“…Prevention of bone and joint deformities was ranked first, prevention of muscular contracture was ranked second, and maintaining and increasing range of motion was ranked third when evaluating participants’ perspectives. However, Hepworth et al [ 30 ] evaluated patient factors when providing splinting therapy for children with neurological impairments and reported that maintaining and improving range of motion ranked first (97.5%), preventing contracture was ranked second (92.5%), and compliance with the caregiver ranked third (90%) per the respondents’ perspectives ( n = 40). In the study of network meta-analysis, hand therapy is important because it proves that Carpometacarpal (CMC) osteoarthritis (OA) patients are best treated with a long thermoplastic carpometacarpal-metacarpophalangeal splint (rigid CMC-MCP) for pain relief, while a short custom-made CMC-MCP splint can be used to improve hand function [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many of the generic tasks and activities mentioned in the articles appear to be the same for occupational therapists in any country (e.g., assessment, education, environmental adaptation, skills training), the context influences therapists' priorities and approach. For example, several authors describe how, in assessment, occupational therapists often rely on informal methods (e.g., observation, interview) or adapt formal measures because most standardised tools are developed in Western countries 34,35 . In terms of interventions, the prevalence of poverty and limited employment opportunities for people with disabilities in various African contexts behoves occupational therapists to focus on vocational skills [36][37][38] , facilitating self-employment 39 and other options for income generation 30,31,40 .…”
Section: Occupational Therapists' Activities: Empowering People To Engage In Meaningful Occupationmentioning
confidence: 99%
“…Unfortunately, there can be discrepancy between evidence and practice, often due to the challenges associated with accessing appropriate research evidence 34,113 . Therefore, research skills are an important component in occupational therapy education in African contexts, and even in countries where research is incorporated as part of standard training (i.e., South Africa), further development is needed 103,114 .…”
Section: The Role Of Occupational Therapy In Africa Related To Researchmentioning
confidence: 99%